2020
DOI: 10.1186/s12958-020-00602-2
|View full text |Cite
|
Sign up to set email alerts
|

Does body mass index impact assisted reproductive technology treatment outcomes in gestational carriers

Abstract: Background: The purpose of this study was to assess whether increased body mass index (BMI) negatively affects assisted reproductive technology (ART) outcomes among gestational carriers. Methods: A retrospective matched case-control cohort, including all gestational carrier (GC) cycles performed at CReATe Fertility Centre (Toronto, ON, Canada) between 2003 and 2016. Setting: A Canadian fertility clinic, with a large surrogacy program. Patients: All gestational carriers that had undergone a cycle completed to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“… 55 BMI was not a predictor of ART outcome in infertile patients. 56 And study has found that BMI has different effects on ART pregnancy and live birth rates depending on race and ethnicity. 57 The different results may be due to differences in the number of cases included in different studies, as well as differences in the definition of BMI classification.…”
Section: Discussionmentioning
confidence: 99%
“… 55 BMI was not a predictor of ART outcome in infertile patients. 56 And study has found that BMI has different effects on ART pregnancy and live birth rates depending on race and ethnicity. 57 The different results may be due to differences in the number of cases included in different studies, as well as differences in the definition of BMI classification.…”
Section: Discussionmentioning
confidence: 99%
“…However, as was recently observed in a systematic review and meta-analysis, no association between prepregnancy subnormal body weight and ART outcomes has been established, and the conclusions in the studies conducted to date have been divergent [18]. While several studies have suggested a lack of a negative association between low BMIs and impaired ART outcomes [19][20][21][22][23][24][25][26][27][28], others have reported decreased numbers of collected oocytes and "good quality" oocytes [29], fewer usable embryos suitable for transfer or cryopreserve [30], an increased risk of miscarriage [15,[31][32][33][34], lower clinical pregnancy and live birth rates [32,34,35], and increased obstetric complications including preterm birth, low birth weight, and small for gestational age neonates [18,[36][37][38] in underweight compared to normal weight women undergoing ART. Based on these ndings, many clinicians recommend weight gain in women with low BMIs who apply for in vitro fertilization (IVF) treatments.…”
Section: Introductionmentioning
confidence: 99%